Pelatihan Pembuatan Modul Ajar Kurikulum Merdeka Belajar MI Khairu Ummah Pekanbaru - Romi Cendra; Rezi Ariawan; Dea Lisma; Andriansyah (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
The problems that occur in the field from the results of interviews with Madrasah Ibtidaiyah (MI) teacher Khairu Ummah said that teachers have not been able to create teaching modules for the independent learning curriculum at all, among the causes are information and knowledge about what teaching modules are, both in theory and in field application. Their knowledge is very minimal, especially regarding the teaching modules of the independent learning curriculum which will just be implemented in the 2022/2023 academic year in the Ministry of Religion of the Republic of Indonesia. The aim of holding training/bimtek is (1) to improve human resources in order to create teachers who are creative, innovative and competitive in accordance with the mandate given by law, thereby producing quality teachers. (2) Providing information and knowledge about creating teaching modules for the independent learning curriculum for madrasah ibtidaiyah (MI) schools. (3) Teachers are able to create teaching modules for the independent learning curriculum according to the standards provided by the Ministry of Religion of the Republic of Indonesia.